Dinamika Kebijakan Kelautan dan Perikanan Kabupaten Rembang Pada Masa Reformasi Tahun 1998-2008 - Salim, Moch (Citra Lekha, 2013)
By using historical method with political history approach, this research concerns on the dynamics of marine and fisheries policies in Rembang Regency as a response and consequence of reformation and regional autonomy. As coastal areas, Rembang responds all the authority delegation with the enactment of regional autonomy through implementation of marine and fisheries policies sectors which has dynamics in line with democratization. The policy transition processes have shown chronologically a significant transformation in the direction of the maritime development paradigm in Rembang Regency despite of its viable evolutionary implementation. Keywords: marine and fisheries sector, autonomy, and reformation